Quaternary geology, geomorphology and tectonics in the Ogosta river valley system, the Danubian plain (Bulgaria) - ANGELOVA, D. (Bulletin of the Geological Society of Greece, 2001)
The Quaternary in the Ogosta River valley system (the Danubian plain) is represented by various genetic types of continental Quaternary sediments (eolian, alluvial, deluvial, proluvial). They lie on a diverse pre-Quaternary base. It is uneven and with various denudation. The accepted correlation schemes are based on local data in which the tectonic factor and duration of deformation have not been accounted for. The present work considers the complex results obtained during the investigation of the Quaternary sediments and formations. The filling consists of clayey-sandy or calcareous-sandy materials, coloured in rusty nuances by iron hydroxides. Their age has been determined on the basis of the found fauna: Elephas meridionalis Nesti,Anancus arvernensis Cr. et Gob (Bakalov, Nikolov, 1962).